APPLICATION OF ANALYTICAL HIERARCHY PROCESS METHOD AS A DECISION SUPPORT SYSTEM IN THE RECRUITMENT OF LECTURERS AT UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI - Dawami, Moh. Fatkur; Fathoni, M. Ivan Ariful; Cindarbumi, Festian (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Each college is obliged to create an ideal ratio of lecturers and students. To improve internal quality or quality on an ongoing basis to meet the ideal ratio of lecturers and students, Universitas Nahdlatul Ulama Sunan Giri always recruits lecturers every year. The file selection flow at the administrative selection stage of lecturer recruitment at Universitas Nahdlatul Ulama Sunan Giri is still carried out conventionally to ensure prospective lecturers are selected to pass to the next stage. The assessment process is subjective, and this can cause inconsistency in the provision of grades in each prospective alternative lecturer. This study aims to design and apply the Analytical Hierarchy Process method to support decisions in the recruitment of lecturers at Universitas Nahdlatul Ulama Sunan Giri. So that in this calculation, the priority of Recruitment of Lecturers at Universitas Nahdlatul Ulama Sunan Giri is obtained as follows; Recent Education 41.22%, GPA 20.61%, Achievement 13.74%, Accreditation 10.3%, Experience 8.24%, and Test 5.89%. Based on the research conducted, the same results were obtained with data in the field that those selected to become lecturers in the mathematics education study program were prospective lecturers with the initials FN, with a total score of 0.1168. The results of applying the Analytical Hierarchy Process method can provide recommendations for selecting alternative lecturer candidates for Universitas Nahdlatul Ulama Sunan Giri who are more objective.